Evaluation Study on Rural Telephony Volume. I - Planning Commission (Planning Commission, 2010)
Development of communications infrastructure is an essential precondition for making available the benefits of liberalization to the rural masses and for further powering the growth engine of the country. It is a central objective of policy that every individual should have access to telecommunication systems of good quality. The importance of telecom in everyone's life has increased enormously, amounting to a paradigm shift. It has become a basic infrastructure like electricity, road, water etc. for the general masses. Telecommunication is essential for implementation of various government schemes related to education, health etc. and also for day to day administration, maintaining law and order etc. However, while urban India has witnessed a telecom revolution the fruits of telecom development have still not adequately reached the rural masses. Recognizing the rural challenges and the potential role played by infrastructure in poverty removal, Government of India initiated the Rural Telephony Programme under the Bharat Nirman Yojana.
Programme Evaluation Organisation Planning Commission Government of India